Natural or artificial? A reflection on a complex ontology. (August 2021) - Cameli, Simone Amato
State-of-the-art planning theory considers cities as cyborg entities composed by a "natural" part (human beings and their social structures) and an "artificial" part (buildings, infrastructure and other urban artifacts). We contend that this hybrid conception is indissolubly coupled with the ability to discriminate perfectly between the "natural" and the "artificial". But is this actually the case? We will provide a critical reflection on this ontological issue pointing out that current urban planning theory as well as the general philosophical reflection is not able to produce a rigorous, consistent epistemic criterion to draw this distinction. Long-standing difficulties in this respect are exponentially amplified by recent developments in artificial intelligence, nanotechnology and biotechnology, and their growing relevance in urban environments of the near future risk making the cyborg conception informing the complexity theory of cities obsolete. We will conclude our reflection identifying a possible path for overcoming this dualism toward a more socio-natural conception internalizing the proteiform character of the concept of "nature" itself as well as its inherent cognitive/political element.